One-step electrochemical synthesis of nitrogen and sulfur co-doped, high-quality graphene oxide. Issue 33 (4th April 2016) - Parvez, Khaled; Rincón, Rosalba A.; Weber, Nils-Eike; Cha, Kitty C.; Venkataraman, Shyam S.
Abstract : Electrically conductive and heteroatom doped, high-quality graphene oxide is prepared by electrochemical exfoliation and without the use of any harsh chemicals. Abstract : High-quality graphene oxide (GO) with high crystallinity and electrical conductivity as well as in situ doped with nitrogen and sulfur is obtained via the electrochemical exfoliation of graphite. Furthermore, iron incorporated GO sheets show promising catalytic activity and stable methanol tolerance durability when used as electrocatalysts for the oxygen reduction reaction.